Discussões sobre gênero e vulnerabilidade a partir da análise de matérias sobre sexualidade das revistas Capricho e Playboy - Pastana, Marcela [UNESP]; Maia, Ana Cláudia Bortolozzi [UNESP] (My University, 2012)
The concept of vulnerability permits the comprehension of the exposition to the infection of the HIV virus without reducing it to the focus in the individual behaviors of non-adoption of the preventive practices, but considering the cultural factors that participate of the context in which these behaviors occur. Among these factors, it is important to consider the gender issues. This qualitative- descriptive study had as an aim to identify the presence of normative patterns of sexuality and gender in articles and sections about sex and sexuality in 18 editions of the Capricho magazine and 10 edition of the Playboy magazine published in 2010, through the content analysis, discussing the relation between the patterns identified and the way how the information about prevention are transmitted by the magazines’ discourses. It was discussed how the lack of information and the way how these patterns are crystallized can contribute to reinforce the vulnerability.

O conceito de vulnerabilidade permite a compreensão da exposição à infecção ao vírus HIV sem reduzi-la ao foco nos comportamentos individuais de não adoção das práticas preventivas, mas considerando fatores culturais que participam do contexto em que os comportamentos ocorrem. Dentre estes fatores, é importante considerar as questões de gênero. Este estudo qualitativodescritivo teve como objetivo identificar a presença de padrões normativos de sexualidade e gênero em matérias e seções sobre sexo e sexualidade de 18 edições da Revista Capricho e 10 edições da Revista Playboy publicadas em 2010, por meio da análise de conteúdo, discutindo a relação entre os padrões identificados e a forma como as informações sobre prevenção são transmitidas pelo discurso das revistas. Discutiu-se como a escassez de informações e a forma como esses padrões são cristalizados podem contribuir para reforçar a vulnerabilidade.
Keywords: Sexuality; Gender; Normative Patterns; Prevention; Vulberability; Vulnerabilidade; Sexualidade; Gênero; Padrões Normativos; Prevenção